2016
DOI: 10.1111/jir.12264
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a condition specific outcome measure for fragile X syndrome: the Aberrant Behaviour Checklist‐utility index

Abstract: The ABC-UI appears to function well as condition-specific outcome measure, and as an indicator of health-related quality-of-life and economic burden in individuals with FXS. Among patients with FXS in the US and their caregivers, significant differences in health care resource utilisation and burden exist across health state utility categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…In fact, once behavioral and emotional problems were covaried, our results showed that families with FXS experienced a greater negative impact on feelings about parenting, finances, siblings, and the degree of difficulty of living with a child or adolescent with FXS. In general, our results are similar to those of other studies (Haessler et al, 2016;Johnston et al, 2003;Lewis et al, 2006;Raspa et al 2016).…”
Section: Article In Presssupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, once behavioral and emotional problems were covaried, our results showed that families with FXS experienced a greater negative impact on feelings about parenting, finances, siblings, and the degree of difficulty of living with a child or adolescent with FXS. In general, our results are similar to those of other studies (Haessler et al, 2016;Johnston et al, 2003;Lewis et al, 2006;Raspa et al 2016).…”
Section: Article In Presssupporting
confidence: 93%
“…In the study by Johnston et al (2003), 25% of mothers of children with FXS felt stress due to isolation and lack of parental competence. Problems and concerns about parenting and family relationships are affected by the diagnostic status of the child, and are greater in the case of parents of children with FXS (Lewis et al, 2006;Raspa et al, 2016).…”
Section: Article In Pressmentioning
confidence: 99%
“…Further financial burden was caused by home and car adaptations and the costs of additional healthcare not covered by public healthcare provision, such as physiotherapy, speech therapy, and occupational therapy [24]. Many families were forced to have at least one caregiver (e.g., mother or father) change their job or working hours, and 35% to 45% of families reported that a caregiver had to leave their job entirely [30,[36][37][38]. Seizures in FXS have been shown to be associated with caregiver financial burden and quitting work [32].…”
Section: Impact On Work and Productivitymentioning
confidence: 99%
“…Twenty-three unique valuation methods were identified. These were grouped into six key categories: (i) VAS—EQ-5D VAS (number of samples = 348; 8.8%), EQ-5D-Y VAS ( n = 232; 5.8%) and stand-alone VAS ( n = 252; 6.3%); (ii) trade-off-based direct valuation methods—TTO ( n = 171; 4.3%), SG ( n = 227; 5.7%), chained gamble and adjusted SG ( n = 143; 3.6%); (iii) adult-specific MAUIs—EQ-5D ( n = 424; 10.7%), SF-6D ( n = 34; 0.9%), AQoL-5D ( n = 16; 0.4%) and 15D ( n = 2; 0.05%); (iv) MAUIs compatible with both childhood and adult populations—QWB ( n = 224; 5.6%), HUI2 ( n = 482; 12.1%), HUI3 ( n = 822; 20.7%), modified HUI (10-dimension variant of HUI [ 41 ], HUI3 with ‘worst imaginable health’ as 0 instead of death [ 42 ]; n = 8; 0.2%) and ABC-UI (Aberrant Behaviour Checklist Utility Index) [ 43 ] ( n = 1; 0.03%); (v) childhood-specific MAUIs—EQ-5D-Y ( n = 108; 2.7%), CHU9D ( n = 231; 5.8%), 16D ( n = 73; 1.8%), 17D ( n = 39; 1.0%), AQoL-6D ( n = 50; 1.3%), PAHOM (Pediatric Asthma Health Outcome Measure) [ 44 ] ( n = 69; 1.7%) and CH-6D (Child Health-6 Dimensions) [ 45 ] ( n = 3; 0.08%);and (vi) mapping non-preference-based clinical measures to utility indices [ 46 50 ] ( n = 15; 0.4%).…”
Section: Resultsmentioning
confidence: 99%